Horse soldiers [compact disc, abridged] : the extraordinary story of a band of U.S. soldiers who rode to victory in Afghanistan - Stanton, Doug (Audioworks, 2009)
Doug Stanton tells the astonishing story of twelve U.S. soldiers who rode horses into Afghanistan immediately following 9/11 to defeat the Taliban.